(untitled) (Swiss Medical Weekly, 2026)
STUDY AIMS: To determine the incidence of mechanical restraint in the emergency department (ED) of the University Hospital of Bern, Switzerland; To assess differences in restraint frequency and practice across patient groups (sex, age, alcohol involvement); To characterise triggers of aggression or agitation and restraint-related interventions including medication use; To examine temporal patterns, particularly the impact of the COVID-19 lockdown and pandemic. METHODS: We included patients presenting at our institution between 1 January 2018 and 30 September 2022 who were subjected to mechanical restraint. Patients were identified through a keyword search followed by a comprehensive full-text review of the hospital database. Demographic and consultation characteristics, data about restraining circumstances and characteristics, as well as referral or discharge procedure were collected. Group comparisons were performed using the Wilcoxon rank-sum test or Kruskal–Wallis test, as appropriate. Categorical variables were compared using the chi-squared test. Incidence rate ratios across the three COVID-19 mitigation phases (pre, during, post) were estimated using Poisson regression. RESULTS: We identified 285 patients who were subjected to mechanical restraint, corresponding to an incidence of 1.22 (95% CI: 1.08–1.37) per 1000 ED consultations during the study period. Men were overrepresented with 67.4% and the median age was 30 years (IQR: 23–41). Alcohol intoxication was the primary trigger of aggression in 35.4% of cases, with mixed intoxication present in 24.2%. The largest subgroup consisted of young men (≤40 years) under the influence of alcohol (31.6%). Compared to men, women were generally younger (28 vs 32 years, p <0.001) and had a higher prevalence of psychiatric comorbidities (43.0% vs 20.3%, p <0.001). Older patients were more likely to be intoxicated with alcohol (52.8% vs 29.6%, p <0.001), whereas younger patients had a higher rate of mixed intoxication (28.2% vs 12.5%, p = 0.007) and psychiatric disorders (31.9% vs 15.3%, p = 0.006). Mechanical restraint involving alcohol was more common in men (74.7%, p = 0.001), associated with risk of harm to others (69.8%, p <0.001) and addiction problems (76.4%, p <0.001). Pharmacological coercive measures were primarily administered using benzodiazepines (78.2%, typically intravenous and/or nasal application) and haloperidol (47.4% intravenous and/or intramuscular). The median duration of mechanical restraint was 258 minutes (IQR: 160–400). Alcohol-involved presentations were significantly associated with young men, non-Swiss nationality, acute risk of harm to others, night shift, addiction and longer restraint times (all p ≤0.001). The number of mechanical restraints increased until mid-2020, stabilising during the COVID-19 mitigation period, with a higher incidence of mechanical restraints during the pandemic (1.43 vs 1.02 per 1000 consultations pre-pandemic, p = 0.008). CONCLUSION: The incidence of mechanical restraint was low (1.22 per 1000 visits). Predominantly, young, intoxicated men, presenting with risk of harm to others, were subject to mechanical restraint. Psychiatric comorbidities were more common in women, who were therefore more likely to pose a risk of self-harm. During the COVID-19 mitigation period, the incidence of mechanical restraint increased; however, the causal factors underlying this trend remain unclear.